Sung taee L. answered • 11/24/12

Teach Concepts, Thinking methods, Step by Step (Physics & Math)

Given equations can be rearranged as below.

5x +2y =29 ------------(1)

43x + 4y + 2z = 29 -----(2)

67x + 3y + 4z = 29 -----(3)

2 times equation (2) gives 86x + 8y + 4z = 58 ------(4)

equation (4) - equation (3) gives 19x + 5y = 29 --------(5)

5/2 times equation (1) gives 25/2 x + 5y = 29x5/2 ------(6)

equation (5) - equation (6) gives (19-12.5)x = (29-5x29/2) therefore x = -6.69

substitute x value to equation (1) gives y = 31.225 and substitute x value and y value to equation (2) gives z = 95.885

When you adding two equations, you have to add left side terms of each equation together and do the same thing for right side as well.